Climate risk management in agriculture : Monthly and seasonal forecast application - Mohanty, U. C.
In India, more than 50% of the population is engaged in agriculture and allied activities, contributing around 18% to the country's Gross Value Added (census report 2021). Further, more than 50% of the total agricultural production comes from a rain-fed area covering 60% of total agricultural land and is highly vulnerable to weather hazards. Seasonal weather variability in terms of droughts, flash floods, heavy rainfall, thunderstorms, cyclones, heat waves, etc. severely affect the agricultural production, particularly the rainfed agriculture and rural economy. To avoid such weather-related risks, weather-based crop planning is essential, thus, seamless accurate weather forecasting is one of the important inputs for agricultural production management.
Includes references and Subject index
Keywords: Forecasting; Risk assessment; Climatic changes